1993
DOI: 10.1056/nejm199304083281404
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Standard Regimen (CHOP) with Three Intensive Chemotherapy Regimens for Advanced Non-Hodgkin's Lymphoma

Abstract: CHOP remains the best available treatment for patients with advanced-stage intermediate-grade or high-grade non-Hodgkin's lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
866
1
40

Year Published

1995
1995
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,965 publications
(940 citation statements)
references
References 25 publications
21
866
1
40
Order By: Relevance
“…These patients should be treated with radiation therapy alone when the disease is localized without nodal involvement. 4 For the rare remaining patients, due to the high relapse rate, we think that chemotherapy is advisable, however, the optimal regimen is not yet known 17 but it must be chosen based on its low early and long-term toxicity in light of the long survival of these patients. For cutaneous B cell lymphoma, radiation therapy alone can only be recommended to patients whose disease is not localized to the leg and has no nodal involvement, nor elevated LDH and a good performance status.…”
Section: Discussionmentioning
confidence: 99%
“…These patients should be treated with radiation therapy alone when the disease is localized without nodal involvement. 4 For the rare remaining patients, due to the high relapse rate, we think that chemotherapy is advisable, however, the optimal regimen is not yet known 17 but it must be chosen based on its low early and long-term toxicity in light of the long survival of these patients. For cutaneous B cell lymphoma, radiation therapy alone can only be recommended to patients whose disease is not localized to the leg and has no nodal involvement, nor elevated LDH and a good performance status.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality for NHL rose at a similar rate, stabilised in the early 1990s and then started to fall at the end of the 1990s. The survival pattern for NHL had not changed significantly in over two decades up to the late 1990s [1] despite attempts to increase the efficacy of the standard treatment, combination chemotherapy (CHOP), with the addition of other cytotoxic drugs [2]. Two pivotal clinical trials in the late 1990s showed that the addition of the monoclonal antibody targeting the CD20 antigen expressed on almost all malignant B cells, rituximab, to standard chemotherapy regimens improved the survival for patients with indolent NHL, and patients with diffuse large B-cell lymphoma (the two commonest NHL subtypes) [1].…”
Section: Introductionmentioning
confidence: 99%
“…A current frontline therapeutic protocol for NPM‐ALK + T‐cell lymphoma is the CHOP polychemotherapy. Alas, severe adverse reactions, including therapy‐related death, are sometimes encountered during clinical utilization of CHOP (Fisher et al ., 1993; Lim et al ., 2010; Sitzia et al ., 1997; Tulpule et al ., 2006). In a previous study from our laboratory, using a full concentration of CHOP in mice with systemic NPM‐ALK + T‐cell lymphoma resulted in significant toxic effects including therapy‐related death (George et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%